Nature and politics in the Roman stoicism: about the vivere naturae and the constitution of cosmopolis in Seneca’s thought - Moiteiro, Carlos Renato (Revista Archai, 2010)
What does the stoicism expect when it proposes to men of its age that they live “according to nature”, and which nature”Ÿs conception ”“ universalist or rationalist ”“ is this concept linked? To Seneca, this notion appears re-exhibited in the shape of involvement between the premise of vivere naturae and the notion that the man is by nature convened to live in political community. This text faces to explore this intersection between “political living” and “to live according to nature” on Seneca”Ÿs thought, searching in this way to get a better comprehension about the Roman Stoicism and its ethical and political propositions